2019
DOI: 10.1002/ange.201910579
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Ruthenium–Iron Oxide Colloidal Heterostructures: Improved Yields in CO2 Hydrogenation to Hydrocarbons

Abstract: Catalytic CO2 reduction to fuels and chemicals is a major pursuit in reducing greenhouse gas emissions. One approach utilizes the reverse water‐gas shift reaction, followed by Fischer–Tropsch synthesis, and iron is a well‐known candidate for this process. Some attempts have been made to modify and improve its reactivity, but resulted in limited success. Now, using ruthenium–iron oxide colloidal heterodimers, close contact between the two phases promotes the reduction of iron oxide via a proximal hydrogen spill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Recently, bimetallic catalysts with Fe as active metal were studied to promote CO2 conversion. [227][228][229][230][231] Especially, addition of Co was found to increase the carbide formation, which was beneficial for the chain propagation reaction. It was also observed that the product selectivity could be tuned by changing the Fe/Co ratio.…”
Section: Standalone Catalystsmentioning
confidence: 99%
“…Recently, bimetallic catalysts with Fe as active metal were studied to promote CO2 conversion. [227][228][229][230][231] Especially, addition of Co was found to increase the carbide formation, which was beneficial for the chain propagation reaction. It was also observed that the product selectivity could be tuned by changing the Fe/Co ratio.…”
Section: Standalone Catalystsmentioning
confidence: 99%
“…For instance, a well-defined model system demonstrated that on the nonreducible alumina support, hydrogen spillover is limited to short distances, with the hydrogen flux decreasing over distance to create a concentration gradient 25 . In-depth understanding of hydrogen spillover can not only help to explain experimental phenomena but also aid the design of advanced catalysts with enhanced catalytic performances [27][28][29][30][31][32][33][34][35] . Being inspired by these researches, we posit that there is an opportunity for an approach to modulating the electronic structure of active sites through regulating hydrogen spillover strength for enhanced catalytic performance.…”
mentioning
confidence: 99%
“…For the purpose of investigating the promoting effect of Ru on Fe with respect to the selective hydrogenation of CO 2 to hydrocarbons, Aitbekova et al [ 141 ] synthesized well-defined Al 2 O 3 -supported “Ru/FeO x heterodimers” ( Figure 8 a) via the successive growth of iron oxide NPs (~13.1 nm) on pre-synthesized Ru NPs (~4.8 nm). Through in situ XAS studies, the authors proposed that the synergistic effect between Ru and Fe is implemented via hydrogen spillover from Ru to neighboring Fe.…”
Section: Colloidal Synthesis In Gas-phase Catalysismentioning
confidence: 99%